Chemotherapy-induced pulmonary complications in cancer: Significance of clinicoradiological correlation - Ekta Dhamija (Indian Journal of Radiology and Imaging, 2020)
Chemotherapy while revolutionizing cancer management by improving survival and quality of life; is also associated with several adverse effects. Lung is the most common organ affected in chemotherapy-related complications, due to either drug toxicity or more commonly due to infections caused by immunosuppression and less commonly due to immune-mediated injury. Radiology, when used in combination with clinical and lab data, can help reach the specific diagnosis or narrow down the differentials. The common radiological patterns of drug toxicity include pulmonary interstitial and airway infiltrates, diffuse alveolar damage, nonspecific interstitial pneumonia, eosinophilic pneumonia, cryptogenic organizing pneumonia, pulmonary hemorrhage, edema and hypertension. Cancer patients are immunosuppressed due to the underlying malignancy itself or due to therapy and are prone to a gamut of opportunistic infections including viral, bacterial, fungal and mycobacterial pathogens. Immune reconstitution inflammatory syndrome (IRIS), a well-known complication in HIV, is now being increasingly recognized in non-HIV patients with immunosuppression. Engraftment syndrome is specifically seen following hematopoietic stem cell transplant during neutrophil recovery phase. Pulmonary involvement is frequent, causing a radiological picture of noncardiogenic pulmonary edema. Thus, radiology in combination with clinical background and lab parameters helps in detecting and differentiating various causes of pulmonary complications. This approach can help alter potentially toxic treatment and initiate early treatment depending on the diagnosis.